Radioimmunotherapy combating biofilm-associated infection in vitro - Ye, Zijian; van der Wildt, Berend; Nurmohamed, F. Ruben H. A.; van Duyvenbode, J. Fred F. Hooning; van Strijp, Jos; Vogely, H. Charles; Lam, Marnix G. E. H.; Dadachova, Ekaterina; Weinans, Harrie; van der Wal, Bart C. H.; Poot, Alex J. (Frontiers in Medicine, 2024)
Background Addressing prosthetic joint infections poses a significant challenge within orthopedic surgery, marked by elevated morbidity and mortality rates. The presence of biofilms and infections attributed to Staphylococcus aureus (S. aureus) further complicates the scenario. Objective To investigate the potential of radioimmunotherapy as an innovative intervention to tackle biofilm-associated infections. Methods Our methodology involved employing specific monoclonal antibodies 4497-IgG1, designed for targeting wall teichoic acids found on S. aureus and its biofilm. These antibodies were linked with radionuclides actinium-225 (225Ac) and lutetium-177 (177Lu) using DOTA as a chelator. Following this, we evaluated the susceptibility of S. aureus and its biofilm to radioimmunotherapy in vitro, assessing bacterial viability and metabolic activity via colony-forming unit enumeration and xylenol tetrazolium assays. Results Both [225Ac]4497-IgG1 and [177Lu]4497-IgG1 exhibited a noteworthy dose-dependent reduction in S. aureus in planktonic cultures and biofilms over a 96-h exposure period, compared to non-specific antibody control groups. Specifically, doses of 7.4 kBq and 7.4 MBq of [225Ac]4497-IgG1 and [177Lu]4497-IgG1 resulted in a four-log reduction in planktonic bacterial counts. Within biofilms, 14.8 kBq of [225Ac]4497-IgG1 and 14.8 Mbq [177Lu]4497-IgG1 led to reductions of two and four logs, respectively. Conclusion Our findings underscore the effectiveness of [225Ac]4497-IgG1 and [177Lu]4497-IgG1 antibodies in exerting dose-dependent bactericidal effects against planktonic S. aureus and biofilms in vitro. This suggests that radioimmunotherapy might serve as a promising targeted treatment approach for combating S. aureus and its biofilm.